A influência da filosofia de Friedrich Nietzsche na obra de Henri Lefebvre: da crítica da vida cotidiana à teoria da produção do espaço - Bruno Siqueira Fernandes (2021)
This dissertation aims to retrace and reconstruct the influence of Friedrich Nietzsche's philosophy in the works of Henri Lefebvre, in particular in the Critique of Everyday Life and in The Production of Space. A joint reading of the two theoretical bodies shows us how the concepts mobilized by the French philosopher refers to a set of properly Nietzschean themes, as in the case of the concepts of culture, style, metaphor, metonymy, will to totality, among others. Thus, we seek to demonstrate the development of each of these concepts and points of contact within the Lefebvrian text, at the same time that we propose a set of new possible readings for the critique of everyday life and for the theory of the production of space based on Nietzsche's philosophy. This interpretation proposal will allow not only to put Henri Lefebvre's theoretical contributions in perspective with the history of philosophy, but also to highlight the importance of Nietzschean thought in the critique of abstract space.